Consumers’ Perception and Performance Appraisal of Mobile Phone Companies in Bangladesh - Islam, Tajul; Hoque, Rajidul; Alam, Md.Ashraful (Global Disclosure of Economics and Business, 2013)
In recent times telecommunication industry like mobile phone, radio link device have made revolution in the world. For the last few years mobile phone has become part and parcel of our daily life. It has become an essential part of business, commerce and society. Mobile phone provide great assistance to users by giving the opportunity to access to the anywhere of the world. Moreover, with the continuous diversification, the use of mobile is not only limited to talking but its use ranges from using internet, sending messages, listening to music, to organizing various works are comfortably completed in time. The use of mobile phone was introduced in Bangladesh at the middle of 1989 by the CityCell Company. Now with the change of time another five operators have introduced in the market. The function of mobile in Bangladesh with its communicative use also spread with value added service like mobile banking, railway ticket purchasing, health services, news update, and examination results and so on. But there are a lot of complain about these operators services. Descriptive analysis, Z-test, Chi-square test and Multiple Regression Analysis were used to test the collected data and hypotheses of the research study. Through this research we have tried to find out consumers perception which impact may be very bad in near future on those operators. Most of the respondents think that mobile operators are charging higher terrify in which customers are deprived from pulse system. Slow internet service, and lack of coverage hamper to the access of information. By conducting this research we have found that except those complain, the overall services of mobile phone are moderately well.JEL Classification Code: D18; D91